2004
DOI: 10.1074/jbc.m403140200
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, an Endogenous-specific Inhibitor of Estrogen Receptor α via Calmodulin

Abstract: Melatonin is an indole hormone produced mainly by the pineal gland. We have previously demonstrated that melatonin interferes with estrogen (E 2 ) signaling in MCF7 cells by impairing estrogen receptor (ER) pathways. Here we present the characterization of its mechanism of action showing that melatonin is a specific inhibitor of E 2 -induced ER␣-mediated transcription in both estrogen response element-and AP1-containing promoters, whereas ER␤-mediated transactivation is not inhibited or even activated at certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 38 publications
5
102
0
1
Order By: Relevance
“…40,41 This further supports the role of ER-␣ in the estrogen-dependent modulation of neoplastic cell growth. A number of different studies showed that proliferation of MCF7 cells induced by 17␤- Figure 7.…”
Section: Discussionsupporting
confidence: 55%
“…40,41 This further supports the role of ER-␣ in the estrogen-dependent modulation of neoplastic cell growth. A number of different studies showed that proliferation of MCF7 cells induced by 17␤- Figure 7.…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, it is important to consider that melatonin is present at much higher levels in some microenvironments-in particular, at inflammatory sites (61). Indeed, inhibition of calmodulin by melatonin was suggested to be involved in many physiological processes, including microtubule polymerization (62), rat myotube-acethylcoline receptor expression (63), neuronal NO synthase expression (64), estrogen receptor a activation (65), and cytoskeleton rearrangement (66) and also to avoid the progression of scoliosis in mice and humans (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Direct actions of melatonin at the tumor cell level include blockage of the ERa but not the ERh receptors (23), effectively becoming a selective estrogen receptor modulator. Furthermore, melatonin interferes with the local synthesis of estrogens by inhibiting aromatases, the enzymes controlling the conversion from androgenic precursors to estrogens.…”
Section: Discussionmentioning
confidence: 99%